Content Analysis of Storytelling Power in Luxury Branding in the Film Mrs. Harris Goes to Paris - Frazna Fadilla Agfalia Herisya (Jurnal Indonesia Sosial Sains, 2025)
This research examines the role of cinematic storytelling in building luxury brand identity, focusing on the film Mrs. Harris Goes to Paris and its depiction of the Dior brand. Using Kapferer and Bastien's Luxury Brand Identity Model, this research explores five key dimensions of luxury branding: exclusivity, craftsmanship, dream factor, symbolic value, and cultural dimension. Through a qualitative content analysis of key scenes, dialogue, and visual elements, the study found that the storytelling in the film effectively highlighted Dior's aspirations and exclusivity, despite criticisms of authenticity and over-commercialization. In addition, sentiment analysis of 342 Google reviews showed that the film's narrative elements were able to create emotional resonance, reinforcing the aspirational and exclusive nature of the Dior brand. The findings provide important insights for academics and practitioners on how storytelling strategies can be used to integrate cultural, emotional and symbolic elements in luxury branding, and maintain brand relevance in a competitive global market. This analysis underscores the importance of authentic and relevant narratives in maintaining credibility and consumer trust in luxury brands.